2019
DOI: 10.3390/jcm8122197
|View full text |Cite
|
Sign up to set email alerts
|

Ceramide Content in Liver Increases Along with Insulin Resistance in Obese Patients

Abstract: The liver plays a central role in the glucose and lipid metabolism. Studies performed on animal models have shown an important role of lipid accumulation in the induction of insulin resistance. We sought to explain whether in obese humans, the insulin resistance is associated with hepatic ceramide accumulation. The experiments were conducted on obese men and women. Each gender was divided into three groups: Normal glucose tolerance group (NGT), Impaired glucose tolerance group (IGT), and Type 2 diabetic subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 41 publications
1
14
0
Order By: Relevance
“…Cer22:0 was also negatively correlated with the suppression of HGO, indicating that it may be involved in the development of insulin resistance. Previous studies have shown Cer22:0 to be increased in livers of people with type 2 diabetes ( Razak Hady et al, 2019 ) and Hi-F fed rodents ( Turner et al, 2013 ; Montgomery et al, 2016 ). Some studies investigating the role of ceramides in liver insulin resistance have implicated Cer16:0 as an important species ( Raichur et al, 2019 ).…”
Section: Discussionmentioning
confidence: 91%
“…Cer22:0 was also negatively correlated with the suppression of HGO, indicating that it may be involved in the development of insulin resistance. Previous studies have shown Cer22:0 to be increased in livers of people with type 2 diabetes ( Razak Hady et al, 2019 ) and Hi-F fed rodents ( Turner et al, 2013 ; Montgomery et al, 2016 ). Some studies investigating the role of ceramides in liver insulin resistance have implicated Cer16:0 as an important species ( Raichur et al, 2019 ).…”
Section: Discussionmentioning
confidence: 91%
“…Liver plays a central role in lipid metabolism . Usually, insulin resistance is hallmarked by the excessive lipid accumulation in liver, further the lipid deposition will give rise to the morphological and functional perturbations of liver. , Raised levels of triglyceride and cholesterol were common in insulin resistance, and have become two focused problems . Currently, looking for a suitable entry point is the linchpin to resolve above matters.…”
Section: Introductionmentioning
confidence: 99%
“…Insulin resistance (IR) is when the tissues are not sufficiently sensitive to insulin's effects despite its normal or more often elevated blood levels. IR, together with obesity and severe systemic inflammation, play a vital role in the development of the so-called metabolic syndrome and cardiovascular diseases, psychiatric disorders, and cancers [ 1 ]. This applies especially to overweight and obese people who are at the highest risk of developing insulin resistance.…”
Section: Introductionmentioning
confidence: 99%